Virtual Legal Culture That Hinders the Rights of Statutory Rape Victim Girls to Receive Protection and Recovery - Ni'mah, Zulfatun (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2024)
A girl who engages in sexual intercourse with an adult man is legally considered a victim of sexual violence in the form of statutory rape, thus entitled to protection and recovery. However, in a statutory rape case involving a teacher and student in Gorontalo in September 2024, the victim's identity was widely disseminated online, complicating the protection and recovery process. This research aims to identify the virtual legal culture that undermines the rights of female victims of statutory rape to receive protection and recovery. The study employs an ethnographic method with a socio-legal approach. Data were collected through virtual observation of TikTok accounts responding to statutory rape cases in Gorontalo and analyzed using content analysis techniques. The results show a series of legal cultures that hinder the fulfillment of the rights of female statutory rape victims to enjoy protection. These include the